Glomerular Endothelial Cell Stress and Cross-Talk With Podocytes in Early Diabetic Kidney Disease - Daehn, Ilse Sofia (Frontiers in Medicine, 2018)
Diabetic kidney disease (DKD) is one of the major causes of morbidity and mortality in diabetic patients and also the leading single cause of end stage renal disease (ESRD) in the United States. A large proportion of diabetic patients develop DKD even with comparable blood glucose levels, indicating a significant genetic component of disease susceptibility. The glomerulus is the primary site of diabetic injury in the kidney, glomerular hypertrophy and podocyte depletion are glomerular hallmarks of progressive DKD and the degree of podocyte loss correlates with severity of the disease. We know that chronic hyperglycemia contributes to both micro- and macrovascular complications, as well as podocyte injury. We are beginning to understand the role of glomerular endothelial injury, as well as the involvement of reactive oxygen species (ROS) and mitochondrial stress, which play a direct role in DKD and in other diabetes complications. There is however, a gap in our knowledge that links genetic susceptibility to early molecular mechanisms and proteinuria in DKD. Emerging research that explores glomerular cell’s specific responses to diabetes and cell crosstalk will provide mechanistic clues that underlie DKD susceptibility and provide novel avenues for therapeutic intervention.